Effect of Hemodialysis On Plasma Osmolarity In Patients With Chronic Renal Failure - Al-Shamma, Yesar M.H.; Aziz, Abdul- Aziz A.; Al-Sunbly, Yihia Mousa; Al-Turjoman, Sadiq MAA. (Journal of the Faculty of Medicine Baghdad, 2008)
Back ground: The study was conducted on fifty patients (27 males and 20 females) with chronic renal failure (CRF) undergoing maintenance hemodialysis (HD), at artificial Kidney unit, Al- Hakeem Hospital / Najaf, during the perioed from April to June 2008. Patients & methods: Plasma osmolarity ( Posm), plasma creatinine (P cr ) plasma urea (P urea)>plasma sodium (P Na)and plasma potassium ( P k )were measured for all patients before and after dialysis. Results: The paired t -test was used to compare the pre-dialysis values with the post dialysis values and simple linear correlation to study the relation between (P Na), and ( Posm), p values less than 0.05 considered not significant. The result of study showed a significant decrease in the means of P Na , P k, P cr, P urea and Posm after dialysis in comparison with the pre-dialysis values ( p<0.0001). There was also a significant positive correlation between P Na and Posm (r=0.30,p<0.05) Conclusions: HD had a significant regulatory effect on body fluids and electrolytes ratio,Posm and removal of uremic toxins in patients with CRF, the study also reviled that Posm may be another useful indicator of body fluids and electrolytes status among these patients